Sensitivity Analyses of The Dynamics of Covid-19 Transmission in Response to Reinfection - Putri, Nurul Qorima; Sianturi, Paian; Sumarno, Hadi (Jambura Journal of Biomathematics (JJBM), 2023)
SARS-CoV-2 brings on the pandemic known as Coronavirus Disease 2019 (Covid-19). The Covid-19 spread model developed by Bugalia et al.(2020) has been modified in this study by incorporating reinfection and covid-19-related death during medical isolation. This model has two equilibrium points: the point of equilibrium without disease and the point of equilibrium with the disease. In addition, the equilibrium point's stability and the basic reproduction number (R0) will be discussed. A sensitivity analysis based on Covid-19 data from India was carried out to identify sensitive parameters. Lockdown's effectiveness is one of the sensitivity analysis parameters that impact changes in R0.